LANGUAGE BEHAVIOUR AND ITS SOCIAL CONSEQUENCE A CASE STUDY OF LANGUAGE AND URBANIZATION - AYU ANGGRAINI, IDA (LANGUAGE HORIZON, 2019)
Language loss is a community that lost their mother tongue for a certain factor. Language loss can occur on two levels (personal or familiar levels). It is proven in American or Indonesian immigrants, that person will lose their mother tongue when they stop speaking in their original language (ByErin Haynes, University of California, Berkeley). Language Loss is also a phenomena language loss from variety of perspective such as neurolinguistics, psycholinguistics and sociolinguistics (Seliger&Vago, 1991). In case I want to explain about factor influencing the speaker language loss in the world by using some journals or article. And I using a research to become a proven in this paper about language loss. The aims this paper to show the reader about language loss more detail and factor influencing human language loss use a research. Keyword : Language Loss; Anomie; Acculturation; Extinction; Reactivation